Seismic analysis using maximum likelihood of gutenberg-richter - Primandari, Arum Handini; Khotimah, Khusnul (Association for Scientific Computing Electrical and Engineering, 2017)
An earthquake is one of catastrophe which often claim numerous lives and cause great damage to infrastructure. Multiple studies from various field have been conducted in order to make a precise prediction of earthquake occurrence, such as recognizing the natural phenomena symptoms leading to the shaking and ground rupture. However, up till now there is no definite method that can predict the time and place in which earthquake will occur. By assuming that the number of earthquake follow Gutenberg-Richter law, we work b-value derived using Maximum Likelihood Method to calculate the probability of earthquake happen in the next few years. The southern sea of D.I. Yogyakarta was divided into four areas to simplify the analysis. As the result, in the next five years the first and second area have high enough probability (>0.3) to undergo more than 6.0-magnitude earthquake.